Fatigue Behaviour of High-Velocity Oxy-Fuel (HVOF) Coated Steel by Finite Element Analysis - Ab Ghani, Muhammad Al Amin; Harimon, Mohd Azhar; Abd Jalil, Muhammad Faris Fauzan (Journal of Advanced Mechanical Engineering Applications, 2023)
High-velocity oxy-fuel (HVOF) spraying is extensively used in a range of industries. This is because it can reduce component wear, erosion, and corrosion. If mechanical qualities and fatigue behaviour are considered, the impact of the HVOF thermal spraying coating on the components can be contested. The major goals of this work are to investigate the fatigue properties of carbon steel coated with tungsten carbide-nickel and to use finite element analysis to investigate the fracture process of carbon steel coated with tungsten carbide-nickel. The fatigue test for these studies was conducted in ANSYS Workbench software, where the mean theory is set as Goodman theory. Specimens are modelled in SolidWorks software in a dog-bone shape. The fatigue test simulations are run with the 9 kN, 10.5 kN, 12 kN and 13.5 kN forces applied to one of the specimens' ends and fixed support applied to the other. Based on the result, the coated specimens can sustain longer compared to uncoated specimens, and the higher forces will reduce the lifespan of the specimen. The results also show that uncoated specimens receive more damage at maximum compared to coated specimens, and the higher forces will make the damage received by the specimen higher. For fatigue strength, the uncoated specimens have higher stress compared to coated specimens, and the higher forces will make the fatigue strength of the specimen higher. The result for the fracture shows that uncoated steel has the largest smooth region compared to coated steel.